Incidence and predictors of groin complication after cerebral neurointervention procedure: single centre study - Usman, Fritz Sumantri; Kastilong, Merlin Prisilia; Kurniawan, Beny; Soleh, Mohammad; Keneddy, Erman; Alaztha, Haekal; Octavinawaty, Lenny (International Journal of Research in Medical Sciences, 2022)
Background: Cerebrovascular disease is characterized by an acute compromise of the cerebral perfusion or vascular which caused morbidity and mortality around the world. The most accurate imaging technique for the evaluation of cerebrovascular system is digital subtraction angiography (DSA), but it can cause many complications, one of the most is groin complication. Our objective was to determine incidence and predictors of groin complication after cerebral neurointervention procedure. Methods: An observational prospective study was conducted in PELNI hospital, from January until June 2021, with a total sample of 246 patients. We observed hematoma that occurred within 24 h after procedure. Data was analysed using SPSS ver 24. Results: There were 246 patients who underwent DSA procedures. The average age of patients was 54.3±11.9 years and the majority were male (59.5%). The incidence of groin complication was 37.4%. The predictors of groin complication evaluated with bivariate analysis were age (p=0.167), gender (p=0.827), frequency of puncture (p=0.178), catheter size (p=0.200), duration of compression (p=0.477), comorbidities (hypertension; p=0.839, diabetes; p=0.178, heart disease; p=0.373), and history of anticoagulant (p=0.022). Multivariate analysis showed that history of anticoagulant (p=0.023, OR=2.118 (95% CI 1.107-4.049) to be the most significant factors contributing to groin complication after the intervention. Conclusions: Groin complications appeared to be the most complications after cerebral neurointervention procedure with incidence rate 37.4% and associated mostly with the history of anticoagulant.